2016
DOI: 10.3109/09537104.2016.1158403
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation, adhesion, inflammation, and aggregation potential are altered in the presence of electronic cigarette extracts of variable nicotine concentrations

Abstract: Tobacco smoke extracts prepared from both mainstream and sidestream smoking have been associated with heightened platelet activation, aggregation, adhesion, and inflammation. Conversely, it has been shown that pure nicotine inhibits similar platelet functions. In this work, we 1) evaluated the effects of e-cigarette extracts on platelet activities and 2) elucidated the differences between the nicotine-dependent and non-nicotine dependent (e.g. fine particulate matter or toxic compounds) effects of tobacco and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 37 publications
2
71
0
3
Order By: Relevance
“…These findings support the notion that e‐cigarettes result in a state of platelet hyperactivity, which underlies, at least in part, the prothrombotic phenotype in the exposed mice. Additionally, these data are consistent with those seen in the e‐cigarette vapor extract–exposed human platelet16 studies, in which several functional responses were enhanced (eg, aggregation). Moreover, our data revealed that the e‐cigarette–exposed platelets are less sensitive to inhibition by PGI 2 , in comparison to those from clean air; which may have also contributed to the thrombosis phenotype in these mice.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These findings support the notion that e‐cigarettes result in a state of platelet hyperactivity, which underlies, at least in part, the prothrombotic phenotype in the exposed mice. Additionally, these data are consistent with those seen in the e‐cigarette vapor extract–exposed human platelet16 studies, in which several functional responses were enhanced (eg, aggregation). Moreover, our data revealed that the e‐cigarette–exposed platelets are less sensitive to inhibition by PGI 2 , in comparison to those from clean air; which may have also contributed to the thrombosis phenotype in these mice.…”
Section: Discussionsupporting
confidence: 87%
“…To this end, it was recently shown that treatment with e‐cigarette extracts enhances platelet activation16; whether such effects would manifest under whole‐body e‐cigarette exposure experimental settings is unknown. Thus, we next sought to investigate the effects of e‐cigarette exposure on G‐protein–coupled receptor agonist–induced platelet aggregation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Bahl et al 2012;Romagna et al 2013;Cervellati et al 2014;Willershausen et al 2014;Scheffler et al 2015aScheffler et al , 2015bSchweitzer et al 2015;Tartell 2015). Hom et al (2016) also reported platelet activation, aggregation, and adhesion under EC vapour extracts in vitro. However, some researchers report no cytotoxicity involved with ECs (Wu et al 2014).…”
Section: Cellular Level Effectsmentioning
confidence: 99%